EFFECTS OF MALARIA INFECTION ON THE HAEMATOLOGICAL AND BIOCHEMICAL PARAMETERS OF PREGNANT WOMEN IN ONITSHA, ANAMBRA STATE, NIGERIA (Journal of Biomedical Investigation, 2024)
Background: Malaria remains a major public health problem in sub-Saharan Africa especially among pregnant women and unborn infants.Aim: The effects of malaria infection on the haematological and biochemical parameters of pregnant women were investigated in Onitsha, Anambra State, Nigeria.Materials and Methods: Venous blood samples were collected from 1500 pregnant women who attended antenatal clinic, in Onitsha, Anambra State, Nigeria. The haematological and biochemical parameters of the malaria positive samples were analysed using automated analysers and Giemsa stained blood films. Data was analysed using Chi-square analysis at level of significance of p
Keywords: Placental malaria; liver function test; low birth weight; Plasmodium falciparum